Efficiency of Ultrasonic Treatment on Postharvest Quality and Bioactive Compounds of ‘Kim Ju’ Guava Fruit During Short-Term Storage at Room Temperature - Supapvanich*, Suriyan; Kijka, Chollawit (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2020)
The purpose of this recent work was to investigate the efficiency of ultrasonic (US) treatment on the postharvest quality and bioactive compounds of ‘Kim Ju’ guava fruits during storage at room temperature (RT) (28±1°C) for 6 d. The fruit samples were sonicated at 40 kHz and 150 w for 10 min. Visual appearance, colour attributes, weight loss, total soluble solids (TSS), titratable acidity (TA), texture, pectin substances, antioxidant activity, total phenols and flavonoids contents of the fruits were monitored during storage. The fruits treated with US had better visual appearance than that of untreated fruits. US treatment could delay weight loss but it had no effect on all colour attributes, TSS and TA of fruits. Fruit softening was inhibited by US treatment due to delay in the formation of increased soluble pectin and decreased insoluble pectin contents. Moreover, US treatment could enhance antioxidant activity and the total phenols and flavonoids contents. Nevertheless, there was no change of ascorbic acid content in fruits during storage. These results suggest that US treatment is an effective postharvest approach, which could preserve postharvest quality and level of bioactive compounds of ‘Kim Ju’ guavas during short-term storage at RT. Keywords: guava; ultrasound; bioactive compound; firmness; fruit *Corresponding author: Tel.: (+66) 900124901 E-mail: suriyan.su@kmitl.ac.th